PENGGUNAAN TEPUNG AMPAS TAHU UNTUK MEDIA PERTUMBUHAN Candida albicans dan Candida sp. - Endah Prayekti; Yauwan Tobing Lukiyono (Journal of Indonesian Medical Laboratory and Science, 2022)
Tofu pulp is a waste that is widely produced along with the increasing need for tofu. The advantages of tofu waste are high nutritional content, cheap and easy to obtain. The by-product of this tofu industry still contains 26.6% protein, 18.3% fat, and 41.3% carbohydrates for every 100 grams. Based on this, tofu pulp has the potential to be used as raw material for Candida spp growth media, replacing the gold standard medium, which is Potato Dextrose Agar. The ability of tofu pulp flour media to support the growth of Candida spp. need to be tested further for the number and morphology of Candida spp. The purpose of this study was to determine whether tofu pulp media could be used as a substitute for Potato Dextrose Agar media for the growth of Candida albicans and Candida spp. This study is an experimental study with a completely randomized design (CRD). The composition of the tofu dregs flour media used includes tofu dregs flour (0, 1, 2, 3, 4, 5gr); dextrose 2gr; agar 1.5gr; and 100mL aquadest.  Candida inoculation on tofu pulp flour and Potato Dextros Agar media was using a streak plate method. Observations included the number of colonies and the morphology of the tested Candida colonies. The number of Candida albicans and Candida sp colonies growing on tofu pulp flour media was much larger than on control media, but the size of the colonies was  small. Colony recovered from  Tofu pulp flour media with a ratio 5gr tofu pulp flour and 2 gr dextrose were 222.5 CFU/10uL for Candida albicans and 148 CFU/10Ul for Candida sp. The test results of Candida growth on gold standard media were 54.5CFU/10uL for Candida albicans and 50 CFU/10uL for Candida sp. Based on the results of this study, tofu dregs flour media was able to support the growth of Candida spp in terms of numbers but was not able to provide large colony sizes as in gold standard media. For further research, different methods can be used in making the media or adding additional materials for nitrogen sources in the media.